An in situ approach for measuring biogeochemical fluxes in structurally complex benthic communities. Issue 5 (3rd February 2019) - Roth, Florian; Wild, Christian; Carvalho, Susana; Rädecker, Nils; Voolstra, Christian R.; Kürten, Benjamin; Anlauf, Holger; El‐Khaled, Yusuf C.; Carolan, Ronan; Jones, Burton H.
Abstract: The exchange of energy and nutrients are integral components of ecological functions of benthic shallow‐water ecosystems and are directly dependent on in situ environmental conditions. Traditional laboratory experiments cannot account for the multidimensionality of interacting processes when assessing metabolic rates and biogeochemical fluxes of structurally complex benthic communities. Current in situ chamber systems are expensive, limited in their functionality and the deployment is often restricted to planar habitats (e.g. sediments or seagrass meadows) only. To overcome these constraints, we describe a protocol to build and use non‐invasive, cost‐effective and easy to handle in situ incubation chambers that provide reproducible measurements of biogeochemical processes in simple and structurally complex benthic shallow‐water communities. Photogrammetry tools account for the structural complexity of benthic communities, enabling to calculate accurate community fluxes. We tested the performance of the system in laboratory assays and various benthic habitats (i.e. algae growing on rock, coral assemblages, sediments and seagrass meadows). In addition, we estimated community budgets of photosynthesis and respiration by corals, rock with algae and carbonate sediments, which were subsequently compared to budgets extrapolated from conventional ex situ single‐organism incubations. The tests highlight the transparency (>90% light transmission) of the chambers and minimal water exchange with the surrounding medium on most substrates. Linear dissolved oxygen fluxes in dependence to incubation time showed sufficient mixing of the water by circulation pumps and no organismal stress response. The comparison to single‐organism incubations showed that ex situ measurements might overestimate community‐wide net primary production and underestimate respiration and gross photosynthesis by 20%–90%. The proposed protocol overcomes the paucity of observational and manipulative studies that can be performed in in situ native habitats, thus producing widely applicable and realistic assessments on the community level. Importantly, the tool provides a standardized approach to compare community functions across a wide range of benthic habitats. We identify multiple experimental strategies, including the manipulation of stressors/factors, and discuss how the method may be implemented in a variety of aquatic studies.